Enhancing Photocatalytic Performance through Tuning the Interfacial Process between TiO2-Assembled and Pt-Loaded Microspheres. (1st March 2012) - Zhang, Jun; Li, Liping; Li, Guangshe
Abstract : This work reports on a simple two-step approach to rutile TiO2 -assembled microspheres loaded by Pt with an aim to tune semiconductor-metal interfacial processes for enhancing the photocatalytic performance. Systematic sample characterizations and structural analysis indicate that Pt loading did not produce any significant influences on the lattice structure of TiO2 -assembled microspheres. Instead, upon Pt loading, Schottky barrier was formed in the interfaces between microspheres and Pt nanoparticles, which inhabited efficiently the recombination of photo-generated electron-hole pairs essential for the photocatalytic activities. In addition, TiO2 microspheres also showed a capacity of electrons storage and releasing as represented by a high dielectric constant, which increased the utility rate of photogenerated electrons. All these structural advantages contribute to the excellent photocatalytic activity under ultraviolet light irradiation. The interfacial process between microspheres and Pt nanoparticles was further tuned through adjusting the loading Pt content of metal Pt. As a consequence, the best photocatalytic activity on TiO2 was obtained at 0.85 wt% Pt loading, above or below which photocatalytic activity was apparently decreased.